Regenerated glass fiber geopolymer concrete material and preparation method thereof
By incorporating recycled glass fiber and alkali activator into concrete to form a three-dimensional network structure, the problems of carbon emissions from cement production and the disposal of waste wind turbine blades have been solved, realizing the application of low-carbon and high-efficiency building materials.
Patent Information
- Application Number
- CN202511068978.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-11-04
AI Technical Summary
In the current technology, cement production faces the problems of limestone resource shortage and high carbon emissions. At the same time, the environmental pollution risk caused by the non-degradability of waste wind turbine blades is lacking, and there is a lack of solutions for green building materials.
Geopolymer concrete material, which combines recycled glass fiber with alkali activator, enhances the mechanical properties of concrete by incorporating glass fiber from crushed waste wind turbine blades into industrial waste residue to form a three-dimensional network structure.
It has enabled the resource utilization of industrial waste, reduced carbon emissions, improved the mechanical properties and crack resistance of concrete, and reduced the risk of environmental pollution.
Smart Images

Figure CN120887681A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of civil engineering building materials technology, and more specifically, to a recycled glass fiber geopolymer concrete material and its preparation method. Background Technology
[0002] Under the dual pressures of limestone resource shortage and high carbon emissions, cement production urgently needs low-carbon alternatives. Meanwhile, the rapidly developing wind power industry generates waste wind turbine blades, whose composite materials (glass fiber / polymer matrix) are difficult to degrade. Traditional landfill or incineration methods pose serious risks of land occupation and environmental pollution. Therefore, developing green building materials is urgently needed to address the challenges of high carbon emissions from cement and the disposal of wind power solid waste. Summary of the Invention
[0003] The purpose of this invention is to overcome the defects of the prior art and provide a recycled glass fiber geopolymer concrete material and its preparation method.
[0004] The technical problem solved by this invention is achieved by the following technical solution.
[0005] This invention provides a recycled glass fiber geopolymer concrete material containing 0.1% to 0.5% recycled glass fiber by volume, which is obtained by crushing waste wind turbine blades.
[0006] The present invention also provides a method for preparing the above-mentioned recycled glass fiber geopolymer concrete material, which includes: mixing industrial waste residue, recycled glass fiber, alkali activator solution, coarse aggregate, fine aggregate and water reducing agent evenly in proportion to obtain the recycled glass fiber geopolymer concrete material.
[0007] The present invention has the following beneficial effects:
[0008] This invention discloses a recycled glass fiber geopolymer concrete material and its preparation method. The material comprises 0.1%–0.5% recycled glass fiber by volume, obtained from the crushing of waste wind turbine blades. The core components of the waste wind turbine blades are glass fiber reinforcement (mainly containing SiO2) and an organic polymer matrix such as epoxy resin. This invention incorporates the recovered recycled glass fiber into geopolymer concrete using industrial waste (blast furnace slag, fly ash) as a binder. This synergistically utilizes both industrial waste and waste wind turbine blades, and significantly optimizes the material's performance. Specifically, the dispersed recycled glass fiber forms a three-dimensional network structure within the matrix, effectively transferring stress and bridging cracks, thereby enhancing the mechanical properties of the geopolymer concrete and effectively delaying cracking. Attached Figure Description
[0009] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0010] Figure 1 A process flow diagram for preparing recycled glass fiber geopolymer concrete material provided by the present invention;
[0011] Figure 2 This is a flowchart of the preparation process for the alkaline activator solution. Detailed Implementation
[0012] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0013] The following is a detailed description of a recycled glass fiber geopolymer concrete material and its preparation method provided by an embodiment of the present invention.
[0014] In a first aspect, embodiments of the present invention provide a recycled glass fiber geopolymer concrete material, which contains recycled glass fiber at a volume ratio of 0.1% to 0.5%, the recycled glass fiber being obtained by crushing waste wind turbine blades.
[0015] Geopolymers are a class of non-traditional cementitious materials formed from potentially active aluminosilicate raw materials activated by alkali under ambient or moderately heated conditions. Under the action of an alkali activator, the reaction products form a three-dimensional network gel structure with [-Si-O-Al-O-] as the basic structural unit. Compared with traditional silicate cement, geopolymers have advantages such as rapid setting and hardening, high early strength, high temperature resistance, and resistance to acid and alkali corrosion, making them a high-performance new type of cementitious material. Furthermore, their main raw materials are typically industrial solid waste, thus reducing carbon emissions while also achieving the resource utilization of industrial waste.
[0016] Waste wind turbine blades are solid waste generated after wind power equipment is scrapped. Their core components are glass fiber reinforcement (mainly containing SiO2) and organic polymer matrices such as epoxy resin. With the rapid development of the new energy industry, the number of waste wind turbine blades has increased dramatically. Their non-degradable nature has led to increasingly serious accumulation problems, occupying land and posing environmental pollution risks. Promoting the resource utilization of these blades has become an urgent task. Geopolymer concrete is brittle and has poor mechanical properties; therefore, incorporating recycled glass fiber enhances its mechanical properties. This approach can synergistically utilize both types of solid waste and optimize material properties.
[0017] In some alternative implementations, the length of the recycled glass fiber is 10–15 mm. Extensive experimental verification has shown that when the length is less than 10 mm, the interfacial bonding area and anchorage length between the recycled glass fiber and the geopolymer matrix are insufficient, making it easy to pull out and difficult to effectively transfer stress and bridge cracks, resulting in minimal improvement in the flexural strength of the material. When the length is greater than 15 mm, it is prone to entanglement and clumping during concrete mixing, forming internal defects, severely damaging the material's homogeneity, and significantly reducing the fluidity and workability of the mixture, making it difficult to achieve compaction during pouring. Furthermore, excessively long fibers are more costly and harder to maintain integrity during recycling and screening. A length of 10–15 mm ensures sufficient anchorage length for effective stress transfer and crack crossing, with controllable negative impacts on workability, thereby effectively improving the mechanical properties of the geopolymer concrete.
[0018] Preferably, the recycled glass fiber is prepared by the following method: waste wind turbine blades are crushed to obtain sheet material, which is then processed into glass fiber bundles with a length that meets the standard through a fiber making system. After screening, glass fibers with a length of 10-15 mm are selected as recycled glass fiber material.
[0019] In some alternative embodiments, the recycled glass fiber geopolymer concrete material comprises a matrix and recycled glass fiber. The matrix comprises the following components by weight percentage: 17.2%–17.6% industrial waste, 10.3%–10.8% alkali activator solution, 42.6%–43.7% coarse aggregate, 28.6%–28.7% fine aggregate, and 0.08%–0.32% water-reducing agent.
[0020] In some alternative embodiments, the industrial waste residue is a combination of blast furnace slag and fly ash, and the industrial waste residue is a raw material for the cementitious material of concrete.
[0021] Preferably, the blast furnace slag is S95 grade granulated blast furnace slag, and the fly ash is Class I F fly ash;
[0022] Preferably, blast furnace slag and fly ash account for 45% to 55% and 45% to 55% of the total amount of cementitious materials, respectively.
[0023] In some optional embodiments, the alkaline activator solution is prepared by mixing Na2SiO3 solution, solid NaOH powder and tap water, and the modulus of the alkaline activator solution is 3.0 to 3.5;
[0024] Preferably, the Na2SiO3 solution is selected from Na2SiO3 solutions with a Baume degree of 40, a SiO2 mass fraction of 26%, a NaO2 mass fraction of 8.15%, and a modulus of 3.3, and the NaOH powder is commercially available analytical grade solid NaOH powder with a purity of ≥96%.
[0025] Preferably, the alkaline activator solution is prepared by the following method:
[0026] S1. Dissolve solid NaOH powder in tap water by stirring to obtain NaOH solution, and then let the NaOH solution stand and cool.
[0027] S2. Mix the NaOH solution obtained in step S1 with the Na2SiO3 solution, stir thoroughly, seal and let stand to cool, and the alkaline activator solution is obtained for later use.
[0028] Preferably, in step S1, the stirring time is 2-3 minutes, the standing time is 3-4 hours and until completely cooled; in step S2, the stirring time is 2-3 minutes, and the sealed standing and cooling time is 18-24 hours.
[0029] In some alternative embodiments, the coarse aggregate is continuously graded crushed stone, comprising: 34% to 36% coarse stone with a particle size of 20 to 31.5 mm, 44% to 46% medium stone with a particle size of 10 to 20 mm, and 19% to 21% fine stone with a particle size of 5 to 10 mm; and the river sand is coarse sand with a fineness modulus of 3.0 to 3.7.
[0030] In some alternative embodiments, the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent.
[0031] In some alternative embodiments, the concrete comprises, by weight, the following components per cubic meter: 1020–1060 kg of crushed stone, 200–220 kg of blast furnace slag, 200–220 kg of fly ash, 670–710 kg of river sand, 140–155 kg of Na₂SiO₃ solution, 15–19 kg of solid NaOH powder, 85–95 kg of tap water, 2.55–12.75 kg of recycled glass fiber, and 1.96–7.86 kg of water-reducing agent.
[0032] Secondly, embodiments of the present invention provide a method for preparing the above-mentioned recycled glass fiber geopolymer concrete material, which includes: mixing industrial waste residue, recycled glass fiber, alkali activator solution, coarse aggregate, fine aggregate and water-reducing agent evenly in proportion to obtain the recycled glass fiber geopolymer concrete material.
[0033] In some alternative implementations, the following steps are included:
[0034] S1. Place industrial waste residue, coarse aggregate, and fine aggregate in a mixer and mix for 2-3 minutes to obtain a uniformly mixed material;
[0035] S2. Pour the prepared alkali activator solution into the mixture and stir for 2-3 minutes, then add the recycled glass fiber and stir for 3-5 minutes, and finally add the water-reducing agent and stir for 3-5 minutes to obtain the recycled glass fiber geopolymer concrete material.
[0036] The present invention will be further described below with reference to embodiments.
[0037] This invention provides a recycled glass fiber geopolymer concrete material, comprising a matrix and recycled glass fibers, wherein the volumetric content of recycled glass fibers in the concrete material is 0.1% to 0.5%, and the matrix comprises the following components by mass percentage: industrial waste 17.2% to 17.6%, alkali activator solution 10.3% to 10.8%, coarse aggregate 42.6% to 43.7%, fine aggregate 28.6% to 28.7%, and high-performance water-reducing agent 0.08% to 0.32%, wherein the sum of the mass percentages of industrial waste, alkali activator solution, coarse aggregate, fine aggregate, and high-performance water-reducing agent is 100%.
[0038] Furthermore, the industrial waste residue is a mixture of blast furnace slag and fly ash, with blast furnace slag and fly ash accounting for 45%–55% and 45%–55% of the total cementitious material, respectively. The industrial waste residue serves as the raw material for the cementitious material of concrete. Even further, the fly ash is Class I, Type F fly ash, and the blast furnace slag is S95 grade granulated blast furnace slag. In some specific embodiments, the fly ash is purchased from Henan Yuanheng Environmental Protection Engineering Co., Ltd., and the slag is purchased from Luoyang Yellow River Tongli Cement Co., Ltd.
[0039] Furthermore, the recycled glass fiber has a length of 10-15 mm and is prepared by the following method: waste wind turbine blades are crushed to obtain sheet material, which is then processed into glass fiber bundles of standard length using a fiber-making system. After screening, glass fibers with a length of 10-15 mm are selected as the recycled glass fiber material. It is worth noting that this invention does not have special requirements regarding the source of the recycled waste wind turbine blade material; methods well-known in the art can be used. In a specific embodiment of this invention, it is preferable to pre-treat the recycled waste wind turbine blade material, preferably including crushing, screening, washing, and drying in sequence. This invention does not have special requirements regarding the specific implementation of the crushing, screening, washing, and drying processes. This invention removes resin and filler dust from the surface of the recycled waste wind turbine blade material through washing.
[0040] Furthermore, the alkali activator solution is prepared by mixing Na₂SiO₃ solution, solid NaOH powder, and tap water, and the modulus of the prepared alkali activator solution is 3.0–3.5. Specifically, the Na₂SiO₃ solution is selected as a 40 Baume solution with a SiO₂ mass fraction of 26%, a Na₂O mass fraction of 8.15%, and a modulus of 3.3; the NaOH is commercially available analytical grade solid NaOH powder with a purity of ≥96%. Furthermore, the alkali activator solution is prepared by the following method: S1, dissolving solid NaOH powder in tap water by stirring to obtain a NaOH solution, and then allowing the NaOH solution to stand and cool; S2, mixing the NaOH solution obtained in step S1 with a Na2SiO3 solution, stirring thoroughly, sealing and allowing it to stand and cool to obtain the alkali activator solution for later use. In step S1, the stirring time is 2–3 minutes, and the standing time is 3–4 hours until completely cooled; in step S2, the stirring time is 2–3 minutes, and the sealing and standing cooling time is 18–24 hours. In some specific embodiments, the Na2SiO3 solution was purchased from Xingheqian Materials Co., Ltd., and the solid NaOH powder was purchased from Tianjin Baishi Chemical Co., Ltd.
[0041] Furthermore, the coarse aggregate uses continuously graded crushed stone with a particle size of 5–31.5 mm. Even further, the crushed stone is distributed proportionally as follows: coarse stone (particle size 20–31.5 mm) accounts for 34%–36% of the total crushed stone, medium stone (particle size 44–46 mm) accounts for 44%–46% of the total crushed stone, and fine stone (particle size 5–10 mm) accounts for 19%–21% of the total crushed stone.
[0042] River sand is coarse sand with a fineness modulus of 3.0 to 3.7. The river sand used should meet the "Standard for Quality and Testing Methods of Sand and Stone for Ordinary Concrete" (JGJ52-2006) to ensure compaction.
[0043] Furthermore, the water-reducing agent is a polycarboxylate-based high-performance water-reducing agent.
[0044] Furthermore, the proportions of each raw material in the recycled glass fiber geopolymer concrete per cubic meter of concrete are as follows: crushed stone 1020–1060 kg, blast furnace slag 200–220 kg, fly ash 200–220 kg, river sand 670–710 kg, Na2SiO3 solution 140–155 kg, solid NaOH powder 15–19 kg, tap water 85–95 kg, recycled glass fiber 2.55–12.75 kg, and water-reducing agent 1.96–7.86 kg.
[0045] This invention also provides a recycled glass fiber geopolymer concrete material, the preparation steps of which are as follows:
[0046] S1. Place industrial waste residue, coarse aggregate, and fine aggregate in a mixer and mix for 2-3 minutes to obtain a uniformly mixed material;
[0047] S2. Pour the prepared alkali activator solution into the mixture and stir for 2-3 minutes, then add the recycled glass fiber and stir for 3-5 minutes, and finally add the water-reducing agent and stir for 3-5 minutes to obtain the recycled glass fiber geopolymer concrete material.
[0048] The particle size distribution of the river sand used in the following examples and comparative examples is shown in Table 1 below:
[0049] Table 1
[0050]
[0051] Comparative Example 1
[0052] The raw materials for preparing recycled glass fiber geopolymer concrete include a base material and recycled glass fibers. The base material consists of the following components by mass percentage: tap water 3.73%, fly ash 8.79%, slag 8.79%, river sand 28.76%, crushed stone 43.14%, solid NaOH powder 0.70%, Na2SiO3 solution 6.09%, water-reducing agent 0.00%, and the volumetric content of recycled glass fibers in the base material is 0.00%.
[0053] Example 1
[0054] The raw materials for preparing recycled glass fiber geopolymer concrete include a base material and recycled glass fibers. The base material consists of the following components by mass percentage: tap water 3.73%, fly ash 8.78%, slag 8.78%, river sand 28.74%, crushed stone 43.11%, solid NaOH powder 0.70%, Na2SiO3 solution 6.09%, water-reducing agent 0.08%, and the volumetric content of recycled glass fibers in the base material is 0.10%.
[0055] Example 2
[0056] The raw materials for preparing recycled glass fiber geopolymer concrete include a base material and recycled glass fibers. The base material consists of the following components by mass percentage: tap water 3.73%, fly ash 8.78%, slag 8.78%, river sand 28.73%, crushed stone 43.09%, solid NaOH powder 0.70%, Na2SiO3 solution 6.08%, water-reducing agent 0.12%, and the volumetric content of recycled glass fibers in the base material is 0.20%.
[0057] Example 3
[0058] The raw materials for preparing recycled glass fiber geopolymer concrete include a base material and recycled glass fibers. The base material consists of the following components by mass percentage: tap water 3.72%, fly ash 8.77%, slag 8.77%, river sand 28.70%, crushed stone 43.05%, solid NaOH powder 0.70%, Na2SiO3 solution 6.08%, and water-reducing agent 0.20%. The volumetric content of recycled glass fibers in the base material is 0.30%.
[0059] Example 4
[0060] The raw materials for preparing recycled glass fiber geopolymer concrete include a base material and recycled glass fibers. The base material consists of the following components by mass percentage: tap water 3.72%, fly ash 8.76%, slag 8.76%, river sand 28.68%, crushed stone 43.02%, solid NaOH powder 0.70%, Na2SiO3 solution 6.07%, and water-reducing agent 0.28%. The volumetric content of recycled glass fibers in the base material is 0.40%.
[0061] Example 5
[0062] The raw materials for preparing recycled glass fiber geopolymer concrete include a base material and recycled glass fibers. The base material consists of the following components by mass percentage: tap water 3.72%, fly ash 8.76%, slag 8.76%, river sand 28.67%, crushed stone 43.00%, solid NaOH powder 0.70%, Na2SiO3 solution 6.07%, and water-reducing agent 0.32%. The volumetric content of recycled glass fibers in the base material is 0.50%.
[0063] Table 2 below shows the dosage of each component in Comparative Example 1 and Examples 1-5 (based on 1 cubic meter of concrete). After curing for 28 days, the compressive strength and flexural strength of the concrete were tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081~2019). The test results are shown in Table 2.
[0064] Table 2
[0065]
[0066]
[0067] It should be noted that, strictly according to the controlled variable method, the composition of the base material in the control group and the experimental group should be the same (e.g., both contain water-reducing agents). However, the necessity of the process supports the design that the core function of the water-reducing agent in concrete is to adjust workability (not to directly enhance strength). Therefore, in Comparative Example 1 (control group), no recycled glass fiber was added because the concrete fluidity met the construction requirements, so no water-reducing agent was used. In Examples 1-5 (experimental groups), the recycled glass fiber increased the viscosity of the concrete, so water-reducing agents were added to maintain workability.
[0068] As shown in the table above, the flexural strength of the geopolymer concrete increases with the increase of recycled glass fiber content. For example, when the volumetric glass fiber content is 0.5%, the flexural strength of the concrete reaches 9.1 MPa, which is 34% higher than that of the control group. During the flexural strength test, the recycled glass fibers in the concrete samples exhibited breakage and pull-out. This is because the glass fibers can bear the transferred stress, effectively reducing stress concentration. Furthermore, the glass fibers form a three-dimensional network structure within the concrete, which acts as a "bridge," further enhancing the mechanical properties of the material and thus improving the flexural strength of the concrete. At the same time, when the recycled glass fiber content is 0.5%, the compressive strength decreases by 2.9 MPa compared to the control group. This is mainly due to the interlaced and uneven distribution of glass fibers in the concrete, which easily leads to fiber agglomeration, thus reducing the compressive strength of the concrete material. If the content of recycled glass fiber is further increased to 0.6%, the results in Table 2 further suggest that: flexural strength may continue to increase slowly (the bridging effect of recycled glass fiber is enhanced), but the increase will be significantly reduced (diminishing marginal effect); compressive strength will further decrease (agglomeration of recycled glass fiber exacerbates internal defects); workability will deteriorate sharply: an ultra-high water-reducing agent dosage (>1.6%) is required to maintain fluidity, leading to increased costs and potentially causing segregation. Therefore, in this invention, the preferred volume content of recycled glass fiber in the polymer concrete material is 0.1% to 0.5%.
[0069] In summary, when recycled glass fiber is incorporated into geopolymer concrete at a volume fraction of 0.2%, both compressive and flexural strengths are higher than those of the control group. Therefore, geopolymer concrete with a volume fraction of 0.2% glass fiber exhibits the best overall performance. However, increasing the recycled glass fiber content also brings the advantage of improved flexural strength. Therefore, in practical applications, it can be used according to specific needs.
[0070] As can be seen from the above, embodiments of the present invention provide a recycled glass fiber geopolymer concrete material and its preparation method. The recycled glass fiber geopolymer concrete material includes a matrix and recycled glass fibers, wherein the volumetric content of recycled glass fibers in the concrete material is 0.1% to 0.5%. The matrix includes the following components by mass percentage: industrial waste 17.2% to 17.6%, alkali activator solution 10.3% to 10.8%, coarse aggregate 42.6% to 43.7%, fine aggregate 28.6% to 28.7%, and water-reducing agent 0.08% to 0.32%. The sum of the mass percentages of industrial waste, alkali activator solution, coarse aggregate, fine aggregate, and water-reducing agent is 100%. The above-mentioned geopolymer concrete material uses industrial waste as a cementing material and incorporates recycled glass fibers made from crushed waste wind turbine blades to enhance the mechanical properties of the material. Compared with the prior art, the solution provided by the embodiments of the present invention has the following advantages and characteristics:
[0071] (1) The industrial waste residue used in the concrete material prepared in this invention is solid waste discharged by industry and construction, realizing the reuse of industrial waste, turning waste into treasure and reducing environmental pollution. Compared with ordinary silicate cement, the concrete material has a simple manufacturing process and requires less production energy consumption, which can reduce CO2 emissions by 60% to 80%, avoiding the problem of consuming a lot of natural resources and energy in the production process of ordinary silicate cement. It is low-carbon and efficient, reducing the damage to the ecology.
[0072] (2) The combination of alkali-activated cementitious materials and recycled glass fibers effectively reduced the brittleness of geopolymer concrete, improved its mechanical properties (such as flexural strength, fracture toughness, and deformation capacity), and significantly delayed the cracking of geopolymer concrete. This is because the dispersed recycled glass fibers form a three-dimensional network in the matrix. When microcracks initiate, the recycled glass fibers transfer stress through bridging, force cracks to deflect or branch to extend their propagation path, and continuously consume a large amount of energy to overcome interfacial friction during the final pull-out process. These synergistic effects significantly enhance the material's resistance to crack initiation and propagation, thereby improving its brittle failure mode and inhibiting the premature appearance and development of macroscopic cracks.
[0073] (3) This invention uses geopolymers to replace traditional silicate cement. Geopolymers are characterized by low calcium content and high aluminum content, which can effectively fix alkaline ions; their dense and stable aluminosilicate network structure and low calcium properties further inhibit the occurrence of alkali-aggregate reaction. Therefore, geopolymer concrete has excellent resistance to alkali-aggregate reaction.
[0074] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A recycled glass fiber geopolymer concrete material, characterized in that: The geopolymer concrete material contains 0.1% to 0.5% recycled glass fiber by volume, which is obtained by crushing waste wind turbine blades.
2. The recycled glass fiber geopolymer concrete material according to claim 1, characterized in that: The length of the recycled glass fiber is 10-15 mm; Preferably, the recycled glass fiber is prepared by the following method: waste wind turbine blades are crushed to obtain sheet material, which is then processed into glass fiber bundles by a fiber-making system, and then screened to obtain recycled glass fiber material with a length of 10-15mm.
3. The recycled glass fiber geopolymer concrete material according to claim 1, characterized in that: The recycled glass fiber geopolymer concrete material comprises a matrix and the recycled glass fiber. The matrix comprises the following components by mass percentage: 17.2%–17.6% industrial waste, 10.3%–10.8% alkali activator solution, 42.6%–43.7% coarse aggregate, 28.6%–28.7% fine aggregate, and 0.08%–0.32% water-reducing agent.
4. The recycled glass fiber geopolymer concrete material according to claim 3, characterized in that: The industrial waste residue is a combination of blast furnace slag and fly ash, and the industrial waste residue is a raw material for the cementitious material of concrete. Preferably, the blast furnace slag is S95 grade granulated blast furnace slag, and the fly ash is Class I F fly ash; Preferably, the blast furnace slag and the fly ash account for 45% to 55% and 45% to 55% of the total amount of cementitious materials, respectively.
5. The recycled glass fiber geopolymer concrete material according to claim 3, characterized in that: The alkaline activator solution is prepared by mixing Na2SiO3 solution, solid NaOH powder and tap water, and the modulus of the alkaline activator solution is 3.0 to 3.
5. Preferably, the alkaline activator solution is prepared by the following method: S1. Dissolve solid NaOH powder in tap water by stirring to obtain NaOH solution, and then let the NaOH solution stand and cool. S2. Mix the NaOH solution obtained in step S1 with the Na2SiO3 solution, stir thoroughly, seal and let stand to cool, and the alkaline activator solution is obtained for later use. Preferably, in step S1, the stirring time is 2-3 minutes and the standing time is 3-4 hours until completely cooled; in step S2, the stirring time is 2-3 minutes and the sealed standing cooling time is 18-24 hours. Preferably, the Na2SiO3 solution is selected from Na2SiO3 solutions with a Baume degree of 40, a SiO2 mass fraction of 26%, a Na2O mass fraction of 8.15%, and a modulus of 3.3, and the NaOH powder is commercially available analytical grade solid NaOH powder with a purity of ≥96%.
6. The recycled glass fiber geopolymer concrete material according to claim 3, characterized in that: The coarse aggregate is continuously graded crushed stone, comprising: 34%–36% coarse stone with a particle size of 20–31.5 mm, 44%–46% medium stone with a particle size of 10–20 mm, and 19%–21% fine stone with a particle size of 5–10 mm. The river sand is coarse sand with a fineness modulus of 3.0–3.
7.
7. The recycled glass fiber geopolymer concrete material according to claim 3, characterized in that: The water-reducing agent is a polycarboxylate-based high-performance water-reducing agent.
8. The recycled glass fiber geopolymer concrete material according to any one of claims 1-7, characterized in that: The concrete, by weight, comprises the following components per cubic meter: 1020–1060 kg of crushed stone, 200–220 kg of blast furnace slag, 200–220 kg of fly ash, 670–710 kg of river sand, 140–155 kg of Na₂SiO₃ solution, 15–19 kg of solid NaOH powder, 85–95 kg of tap water, 2.55–12.75 kg of recycled glass fiber, and 1.96–7.86 kg of water-reducing agent.
9. A method for preparing recycled glass fiber geopolymer concrete material according to any one of claims 1-8, characterized in that: It includes: Industrial waste residue, recycled glass fiber, alkali activator solution, coarse aggregate, fine aggregate, and water-reducing agent are mixed evenly in proportion to obtain the recycled glass fiber geopolymer concrete material.
10. The preparation method according to claim 9, characterized in that: Includes the following steps: S1. Place industrial waste residue, coarse aggregate, and fine aggregate in a mixer and mix for 2-3 minutes to obtain a uniformly mixed material; S2. Pour the prepared alkali activator solution into the mixture and stir for 2-3 minutes, then add the recycled glass fiber and stir for 3-5 minutes, and finally add the water-reducing agent and stir for 3-5 minutes to obtain the recycled glass fiber geopolymer concrete material.
Citation Information
Cited By
Concrete slab for resource utilization of waste wind power blade FRP and design method
CN122061558A